Identification, Characterization, and Ultrastructure Analysis of the Phenol-Degrading Rhodococcus erythropolis 7Ba and Its Viable but Nonculturable Forms - Valentina N. Polivtseva; Anton N. Zvonarev; Olesya I. Sazonova; Yanina A. Delegan; Yulia N. Kocharovskaya; Alexander G. Bogun; Nataliya E. Suzina (Microorganisms)
Phenol and its chlorinated derivatives are introduced into the environment with wastewater effluents from various industries, becoming toxic pollutants. Phenol-degrading bacteria are important objects of research; among them, representatives of the genus Rhodoccocus are often highlighted as promising. Strain 7Ba was isolated by enrichment culture. A new isolate was characterized using culturing, biochemistry, high-throughput sequencing, microscopy (including electron microscopy), and functional genome analysis. Rhodococcus erythropolis strain 7Ba is able to grow on phenol and chlorophenols without losing its properties during long-term storage. It was shown that strain 7Ba is able to form viable but nonculturable (VBNC) forms during long-term storage under nutrient limitation, preserving both cell viability and the ability to degrade phenols. The ultrastructural organization of the vegetative forms of cells and VBNC forms was characterized. The following distinctive features were found: modifications (thickening) of cell membranes, cell size reduction, nucleoid condensation. Functional analysis of the genome showed the presence of genes for the degradation of alkanes, and two branches of the β-ketoadipate pathway for the degradation of aromatic compounds. Also, the genome of strain 7Ba contains several copies of Rpf (resuscitation promoting factor) genes, a resuscitation factor of resting bacterial forms. The new isolate strain 7Ba is a promising biotechnological agent that can not only utilize toxic aromatic compounds but also remain viable during long-term storage. For this reason, its further application as an agent for bioremediation can be successful under changing conditions of climate and given the deficiency of nutrient compounds in nature. Minor biostimulation will allow the strain to recover its metabolic activity and effectively degrade pollution.